Analisis Kesalahan Siswa SMP dalam Menyelesaikan Masalah Setara Asesmen Kompetensi Minimum Numerasi dan Bentuk Scaffolding yang Diberikan - Fildzah, Natasya Nurhusnina; Masriyah, Masriyah (MATHEdunesa, 2024)
Numeracy is the ability for thinking to use concepts, procedures, facts, and a mathematical tool for explaining many events, problem solving, or retrieving decisions in daily life. The equivalent problem of AKM numeracy description type is the question that equivalent to the minimum assessment of question that developed by government by getting used to critical thinking through the context of daily life that it can not be solved by routine procedures but rather through using the concepts, procedures, facts and mathematical tools to solve problems and their answers are demanding students to express these ideas in the form of written description. This research aims to describe the types of students errors to make problem solving that equivalent to numeracy of AKM, the causal factors, and scaffolding form to minimize these errors. Based on the results of the AKM numeracy test, the researcher choose 3 students of grades of junior high school at SMPN 25 Surabaya as subjects in this research are suitable of established criteria. The data collection technique is carried out by giving tests problems equivalent to AKM numeracy and interviews. Data analysis techniques are carried out based on indicator of student errors. The results obtained in this research are the types of errors made by students include of reading errors, can not read correctly of the words or terms or symbols that contained in the problem and can not read correctly the information contained in the problem, comprehension errors, can not explain correctly about what they know and ask of the problem, and can not explain the problem by using their own words, transformation errors, can not explain the relationship of concepts about problem solving correctly and can not make systematic steps in process of problem solving correctly, process skills errors, can not calculate correctly, can not use mathematical rules correctly, and can not process further solutions correctly of the problem, and encoding errors, can not write the conclusions correctly. Research results shows that students still doing errors to solve the problem that equivalent to AKM numeracy, so they need scaffolding in the form of : questions, instructions, reminders, directions, or encouragement to minimize their errors. The scaffolding is given by researcher adjusted to the errors made by students in completing the test that equivalent to AKM numeration.